The Level of Coverage of Dog Vaccination Against Rabies in Moiben Sub-County, Uasin Gishu County, Kenya - Tuwei, Philip Kipchoge; Kariuki, Stephen Mwaura (European Scientific Journal, ESJ, 2017)
Background: Dog bites and subsequent transmission of rabies virus continue to be a public health threat in some parts of the world. While prophylaxis has proven successful in limiting transmission of rabies virus, dog vaccination coverage has been far below the WHO-recommended level of 75% in many parts, particularly in Africa and Asia. Aim: The aim of this study was to determine the level of dog vaccination coverage in Moiben Subcounty of Uasin Gishu County, Kenya. The study also sought to investigate the reasons for possible low dog vaccination coverage. Methodology: The dog owners were interviewed using structured questionnaires on whether they had their dogs vaccinated, the frequency of vaccination and the number of dogs maintained per household. The respondents were also interviewed on whether their dogs were confined or not and whether they had bitten residents or not. Data was entered into SPSS version 22 of 2013 for analysis. The data was analyzed using chi square and the statistical significance determined at critical p-value of 0.05 and 0.01 in some cases. Results: The coverage of dog vaccination against rabies virus in Moiben Sub-county, Uasin Gishu County was found to be 19.5% (130/666). The number of dogs that had not been vaccinated were 536 out of 666 accounting for 80.5% of the sample in this study. It was established that 32.7% of dogs kept in singles per household and 5.9% of dogs kept in more than 4 dogs per household were vaccinated. The findings show that number of dogs kept by each household is significantly associated (X²=32.2) with the level of vaccination coverage. We also found that a total of 351 (54.6) children below 15 years were the majority who had been bitten by dogs (X² =26.3, p= 0.01) while the least bitten were those above 46 years of age. It was also established that the unconfined dogs (487/75.7%) significantly bit more people than those that were partially confined (X² =12.9, p= 0.01) Conclusion and Recommendation: The dog vaccination coverage at 19.5% in Moiben Subcounty is far below the 75% level recommended by the WHO. The frequency of dog vaccination was found to be once a year among some dog owners, twice among a few others, and once in the life-time of the dog among some dog owners. There was an inverse proportionality between vaccination frequency and the number of dogs owned per household. Dog confinement limits dog bites and hence should be enforced among dog owners. This study recommends that households in Moiben Sub-county keep the number of dogs that they can manage with regards to vaccination to be able to control rabies virus transmission. The county government of Uasin Gishu should move with speed to make and implement a policy on dog ownership to regulate the number of dogs owned per household.